The State of State Reform in Latin America - Lora, Eduardo (Palo Alto, CA : Stanford University Press, 2012)
This book examines four major areas of institutional reform: a) political institutions and the state organization; b) fiscal institutions, such as budget, tax and decentralization institutions; c) public institutions in charge of sectoral economic policies (financial, industrial, and infrastructure); and d) social sector institutions (pensions, social protection, and education). In each of these areas, the authors summarize the reform objectives, describe and measure their scope, assess the main outcomes, and identify the obstacles for implementation, especially those of an institutional nature.